Resultados preliminares do tratamento de insuficiência venosa grave com termoablação da veia safena magna por técnica endovascular com laser de diodo 980nm desenvolvido no Brasil, associado à escleroterapia com polidocanol - Bertanha, Matheus [UNESP]; Sobreira, Marcone Lima [UNESP]; Camargo, Paula Angelelli Bueno [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; Mariúba, Jamil Victor Oliveira [UNESP]; Moura, Regina [UNESP]; Bagnato, Vanderlei Salvador [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2017)
The endovenous laser ablation (EVLA) of the insufficient saphenous vein has similar results to open conventional surgery, but less morbidity. The echo-guided polidocanol foam sclerotherapy technique has been used for the same purpose. The combined techniques may play a role for more severe diseases, such as those with varicose ulcers. An EVLA device (called VELAS) has been developed in the Optics and Photonics Research Center of USP-São Carlos in agreement with FMB-UNESP. In this study, we present the preliminary results of the VELAS device (MMO 980nm diode) in patients with chronic venous ulcer, associated with echo-guided polidocanol foam sclerotherapy for the treatment of varicosities. Primary outcomes were healing time of the venous ulcer, occlusion of the treated veins and treatment-related adverse events. We included 12 patients with insufficient saphenous vein and chronic venous ulcer. Initially, we treated all of them with thermoablation of the insufficient saphenous vein (VELAS), on an outpatient basis, with local anesthesia. After one week of the procedure, we sclerosed the varicosities with polidocanol foam (Tessari technique). The national VELAS device was easily handled. Total venous occlusion occurred in 83.3% of the patients (in seven days) and the association of the techniques was responsible for a wound healing rate of 83.3%, with no adverse events.
Preliminary results of severe venous insufficiency treatment with thermal ablation of the great saphenous vein by endovascular technique with laser diode 980nm developed in Brazil, associated with sclerotherapy with polidocanol
Keywords: Laser coagulation; Laser therapy; Varicose ulcer; Varicose veins; Venous insufficiency